2018
DOI: 10.1159/000492959
|View full text |Cite
|
Sign up to set email alerts
|

The Persevering Cytotaxonomy: Discovery of a Unique XX/XY Sex Chromosome System in Catfishes Suggests the Existence of a New, Endemic and Rare Species

Abstract: The genus Hypostomus has a broad geographic distribution in Brazilian rivers and comprises armored catfishes with a very complicated taxonomy due to the absence of morphological autapomorphies. The existence of nearly 10 allopatric populations with different karyotypes suggests that Hypostomusancistroides represents a species complex in the Upper Paraná River basin. In this paper, an unusual karyotype of an isolated H. aff. ancistroides population was investigated. All specimens of this sample have 2n = 66 chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The proto-Y chromosome in the genome of H. soniae is larger than the X chromosome, as observed in the Y chromosome of H. aff. ancistroides analyzed by Rocha-Reis et al (2018). Thus, the larger size of the proto-Y chromosome may be the result of the apparent accumulation of heterochromatin, mediated by transposable elements, which may play an important role in the differentiation process, as observed in other species of fish (see Chalopin et al 2015).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The proto-Y chromosome in the genome of H. soniae is larger than the X chromosome, as observed in the Y chromosome of H. aff. ancistroides analyzed by Rocha-Reis et al (2018). Thus, the larger size of the proto-Y chromosome may be the result of the apparent accumulation of heterochromatin, mediated by transposable elements, which may play an important role in the differentiation process, as observed in other species of fish (see Chalopin et al 2015).…”
Section: Discussionmentioning
confidence: 74%
“…The proto-sex chromosomes of H. soniae were also characterized by the presence of 18S rDNA cistrons. The association between the 18S rDNA sites and sex chromosomes has been reported in fishes (Artoni and Bertollo 2002, Chen et al 2008; Cioffi and Bertollo 2010), including in the genus Hypostomus (Rocha-Reis et al 2018). Repetitive sequences have been recorded at high frequencies in heterochromatic sex chromosomes and Chalopin et al (2015) linked the evolution and emergence of sex chromosomes to the dynamics of the repeats and transposable elements.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Almost all living organisms possess some karyotype plasticity, although, in certain groups, large plasticity can be considered a characteristic biological trait. This is the case in several groups of fish, especially in the tetras of the genus Astyanax (Characiformes) and in the Hypostomus (Siluriformes) plecos, which may have led to the chromosomal radiation present in these groups (for a review see Pazza and Kavalco 2007;Rocha-Reis, et al 2018). This was also observed in species of Chromaphyosemion (Cyprinodontiformes), especially in C. riggenbachi (Völker et al 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Although variable when observing the totality of the karyotype macrostructure, the presence of C-banding in some chromosomes of all karyomorphs may indicate the existence of some homology (Rubert et al 2011;Fernandes et al 2012;Maurutto et al 2012;Pansonato-Alves et al 2013;Traldi et al 2013;Lara-Kamei et al 2017;Rocha-Reis et al 2018), and may even be considered a phylogenetic sign. In this study, we observed the presence of conserved C+ blocks in pairs of chromosomes 4 (m), 7 (sm) and 26 (a), in a pericentromeric or subterminal region (Figures 2 and 4).…”
Section: Discussionmentioning
confidence: 99%